PENINGKATAN KETERAMPILAN MENYIMAK BERITA MENGGUNAKAN METODE LISTENING ON ACTION DAN TEKNIK RANGSANG TEKS RUMPANG MELALUI MEDIA AUDIOVISUAL PADA SISWA KELAS VIII SMP NEGERI 35 MAKASSAR - Lamere, Nurtina; Asdam, Muhammad; Angreani, A. Vivit (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This study aims to describe the increase in news listening skills using the Listening on Action Method and the Rumpang Text Stimulation Technique through Audiovisual Media in Online Learning of Class VIII.8 Students of SMP Negeri 35 Makassar with a total of 32 students. The data collection techniques using tests and observations. The results of the study show that the ability to listen to news using the Listening on Action Method and the Stimulation of Gaps in Text Through Audiovisual Media of Online Learning has shown good results. After doing II cycles. This is evident in the first cycle, the average value obtained by students was 66.87%, while the second cycle increased to 79.22%. It can be concluded that the increase in the ability to listen to news using the Listening on Action Method and the Stimulation Technique of Gaps in Text through Audiovisual Media in Class VIII Students of SMP Negeri 35 Makassar is increasing